Pengetahuan Ibu tentang 1000 Hari Pertama Kehidupan dan Status Gizi Balita - Adenta Hafizha Aini; Lenny Oktorina ; H. Pandith Arismunandar (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
The first thousand days of life is the golden period where children grow and develop optimally. Nutritional status affects the growth and development of toddlers, including intelligence. The aim of this research was to determine the correlation between maternal knowledge about the first 1000 days of life and the nutritional status of toddlers. This analytical research design was cross-sectional. This research involved 42 mothers with children under five as respondents, who were chosen randomly. Data was collected by filling out questionnaires for level of knowledge and anthropometric measurements for nutritional status of toddlers. The statistical test used for hypothesis testing was Spearman Rank correlation analysis. The results of this analysis showed that the p value = 0.000, with a correlation coefficient = 0.981. It was concluded that there was a strong positive correlation between maternal knowledge regarding the first 1000 days of life and the nutritional status of toddlers.Keywords: knowledge; First 1000 days of life; nutritional status; toddler ABSTRAK Seribu hari pertama kehidupan merupakan golden period di mana anak tumbuh dan berkembang secara optimal. Status gizi mempengaruhi pertumbuhan dan perkembangan balita, termasuk kecerdasan. Tujuan penelitian ini adalah untuk mengetahui korelasi antara pengetahuan ibu tentang 1000 hari pertama kehidupan dengan status gizi balita. Desain penelitian analitik ini adalah cross-sectional. Penelitian ini melibatkan 42 ibu yang mempunyai anak balita sebagai responden, yang dipilih secara random. Data dikumpulkan melalui pengisian kuesioner untuk tingkat pengetahuan dan pengukuran antropometri untuk status gizi balita. Uji statistik yang digunakan untuk pengujian hipotesis adalah analisis korelasi Spearman Rank. Hasil analisis tersebut menunjukkan bahwa nilai p = 0,000, dengan koefisien korelasi = 0,981. Disimpulkan bahwa ada korelasi positif yang kuat antara pengetahuan ibu mengenai 1000 hari pertama kehidupan dengan status gizi balita.Kata kunci: pengetahuan; 1000 hari pertama kehidupan; status gizi; balita